The Philosophy of Tai Chi Chuan. Wisdom from Confucius, Lao Tzu and Other Great Thinkers (Revista de Artes Marciales Asiáticas, 2012)
Freya y Martin Boedicker. Berkeley (California): Blue Snake Books, 2009. 98 páginas. 21,5x13 cm. I.S.B.N.: 978-1-58394-263-5.